Pedro's circuits in the city of São Paulo: religiosity and homelessness - Debora Galvani; Denise Dias Barros (Interface: Comunicação, Saúde, Educação, 2010)
This is a case study based on the reconstitution of the life history of a homeless adult person in São Paulo City. Ethnographic research and life history were the strategies in a 12-month long data collecting. Analysis tried to reveal, in the process of identity construction, singularities able to re-signify and confer historicity to homeless experience. To discuss Pedro’s path, religiosity analysis is a crucial element for re-assessing his homelessness history. Allied to other nets, religiosity showed different possibilities of constructing interdependence nets, thus characterizing re-signifying and sense reconstructing movements, and eluding disaffiliation processes so frequent in the case of people that experience rupture conducting to homelessness. In those processes, the socially negative identity linked to homelessness can be dislodged and widened, acquiring more elucidative delineations and dynamics. Nonetheless, there is always the need and the challenge of constructing collective alternatives to precarious homelessness experience.